Rapid and Simple Amplification of Genomic DNA Sequences Flanking Transposon - ARIS TRI WAHYUDI (Indonesian Society for microbiology, 2007)
A rapid and simple method to amplify genomic DNA sequences flanking mini-Tn5 transposon insertion was developed. This technique can be used to determine the location and orientation of the transposon insertion within genomic DNA of the bacteria. Based on the mini-Tn5Km1 transposon sequence, PCR primers can be designed to specifically amplify the DNA sequences flanking mini-Tn5 transposon by inverse polymerase chain reaction (inverse PCR) directly, upstream and downstream of the transposon insertion. The method involves: (i) digestion with a restriction enzyme that does not cut mini-Tn5Km1 sequence; (ii) self-ligation under conditionsfavoring the production of monomeric circles; and (iii) inverse PCR reaction using primers designed from mini-Tn5Km1 sequence to amplify the DNA sequences flanking mini-Tn5Km1 transposon insertion. Feasibility and reliability of this method were demonstrated with mini-Tn5Km1 mutants of the microaerobic magnetic bacterium Magnetospirillum magneticum AMB-1 which are defective in magnetosomes synthesis. The inverse PCR products amplified from these mutant genomes showed the correct fragments as determined through Southern hybridization and DNA sequence analysis.